2016
DOI: 10.1002/ffj.3316
|View full text |Cite
|
Sign up to set email alerts
|

On the persistence of mouse urine odour to human observers: a review

Abstract: To the human nose, mice produce unique, persistent and potent odour which is widely assumed to be derived mainly from their urine. In this review, we discuss why the mouse odour is so potent and long-lasting to the human nose. Sensory and chemical analyses have revealed that 2-sec-butyl-4,5-dihydrothiazole (SBT) was the major mousy odorant and present almost exclusively in male urine. It is not depleted from urine even after repeated headspace or solvent extractions since its majority is tightly bound to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 109 publications
0
4
0
2
Order By: Relevance
“…House mice ( Mus musculu s) excrete large quantities of major urinary proteins (MUPs) that bind and transport hydrophobic ligands, including several volatile pheromones 13 . Upon excretion, MUPs slow down the release of volatiles from scent marks 48 , which may prolong their attraction and influence on conspecifics. MUPs are often suggested to show high individual diversity and thereby mediate individual and kin recognition 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…House mice ( Mus musculu s) excrete large quantities of major urinary proteins (MUPs) that bind and transport hydrophobic ligands, including several volatile pheromones 13 . Upon excretion, MUPs slow down the release of volatiles from scent marks 48 , which may prolong their attraction and influence on conspecifics. MUPs are often suggested to show high individual diversity and thereby mediate individual and kin recognition 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The pungent smell of synanthropic mice species, sensed by humans, is largely determined by sulfur-containing compounds ( Mucignat-Caretta et al 2010 ), particularly, 2- sec -butyl-4,5-dihydrothiazole (SBT) ( Kwak et al 2016 ). SBT is a pheromone stimulating male aggression ( Novotny et al 1985 ), and is also confirmed to be an alarm pheromone in house mice, excreted by both males and females in case of fear ( Brechbühl et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brechbühl et al (2013) identified sulfur-containing alarm pheromone 2sec-butyl-4,5-dihydrothiazole (SBT) in mice, which shares its chemical structure with TMT, a fearful substance isolated from fox feces (Vernet-Maury et al, 1984). SBT is the major mousy odorant and present almost exclusively in male urine; it is not depleted from urine even after repeated headspace or solvent extractions since its majority is tightly bound to the major urinary proteins (MUPs) (Kwak et al, 2016). Interestingly, the results of another recent research indicated that TMT can also negatively affect reproductive outcome in mice (Adduci et al, 2019).…”
Section: Effects In Malesmentioning
confidence: 99%